To solve this equation, you need to get x by itself, which basically means that you'll need to "undo" everything that has been done to tie up the x.
First, go ahead and factor in the 3 to get rid of the parentheses:
-8+3(x-3)=-2
-8 + 3x - 9 = -2 (note that the 9 is negative because we took a positive 3 times a negative 3 [since that's what "minus 3" really means], and positive times negative is negative. If you multiply 2 positives or 2 negatives, then the result is positive.)
Add the -8 and -9:
-17 + 3x = -2
I can switch the terms around on the LH side just to make it look prettier:
3x - 17 = -2
Now, to get x by itself, we first need to undo subtracting by 17. To do that, we're just going to add 17 to both sides:
3x - 17 + 17 = -2 + 17
3x = 15
Now x is being multiplied by 3 - we need to undo that, too. So divide both sides by 3:
(3x)/3 = 15/3
x = 5
Hope this helps with understanding how the signs change!
2007-01-15 07:17:17
·
answer #1
·
answered by Lola 3
·
1⤊
0⤋
First: eliminate parenthesis - use distribution > multiply the outer term with the terms in the parenthesis...
- 8 + 3(x) - 3(3) = - 2
- 8 + 3x - 9 = - 2
Sec: combine "like" terms...
-17 + 3x = - 2
Third: add 17 to both sides...
-17 + 17 + 3x = - 2 + 17
3x = 15
*Solve for "x" by isolating it on one side - divide both side by 3...
3x/3 = 15/3
x = 5
2007-01-15 07:47:04
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
x = 5 Here's how - -8+3x-9=-2 then -17 +3x=-2 Add 17 to both sides and you are left with 3x=15 divide both sides by 3 so x=5
2007-01-15 07:13:44
·
answer #3
·
answered by Blue-Eyed Guy 3
·
1⤊
0⤋
-8 + 3(X-3) = -2
Combine like signs.
-8 + 3(X-3) = -2 + 8
(When a number passes over the equals sign the sign changes ex. positive to negative and vice versa)
3(X-3) = 6
Now multiply.
3X - 9 = 6
3X - 9 = 6
+9 +9
---------------------
3X = 15
Now divide.
3X = 15/3
X = 5
2007-01-15 07:12:27
·
answer #4
·
answered by Jillian Iris 2
·
1⤊
0⤋
so let's just work with the factor...
3(x-3)
to factor that out you multiply 3 by EVERYTHING inside of the brackets, so
3*x and 3*(-3)
so you would get
(3x - 9)
Now that we have that factored out let's add the rest of the equation
-8 + (3x - 9) = -2
Time to isolate the x add 8 to both sides
3x-9=(-2 +8)
3x-9 = 6
Now add the 9
3x = 15
divide 3
x = 5
And you got it ;)
2007-01-15 07:08:18
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
-8+3(x-3)=-2
-8+3x-9= -2 (distributive)
3x-17= -2 (combine like terms)
3x= 15 (add 17)
x= 5 (divided by 3)
2007-01-15 07:07:19
·
answer #6
·
answered by 7
·
1⤊
1⤋
-8+3(x-3)=-2
3(x-3) = 8-2
3x - 9 = 6
3x = 15
x = 5
2007-01-15 07:05:53
·
answer #7
·
answered by mandeep 3
·
1⤊
0⤋